Development and use of a clinical-community nursing information system in a Bachelor's degree program. - Roa-Díaz, Zayne Milena; Troconis, Emilio Justiniano Carcamo; Henao, John Anderson García; Alfonso, Luz Eugenia Ibáñez (Online Journal of Nursing Informatics)
Purpose: The purposes of this study were, first, to describe the development and implementation of a Clinical-Community Nursing Practice Information System (SIPCE) based upon standardized languages from the International Nursing Diagnostic Association of North America (NANDA-I ), the Nursing Intervention Classification (NIC) and the Nursing Outcomes Classification (NOC); and, secondly, to describe SIPCE's data-based services for the academic and research development of students and professors of the nursing program of the Industrial University of Santander (UIS). Methods: In this paper, the information collected in SIPCE from January 2015 to June 2018 is used. During this time, 11,039 records of care plans that students made during their academic training in different health institutions were collected. The SIPCE software, developed in collaboration with the UIS's Systems Engineering School, was updated with the latest standardized nursing languages (NANDA-I -NIC-NOC). Results: The nursing care plans registered in SIPCE were used to identify the main priorities of care, nursing diagnoses, interventions and outcomes. Also, SIPCE enables the evaluation of each student's academic performance and consolidates the students' and professors' work in clinical and community environments. Conclusions and implications: The SIPCE software helps nursing process documentation, implementation and teaching through the care plans data exploitation obtained from the clinical and community students' training. As a result, the main trends in nursing care using standardized language are shown through the use of this software as an observatory for nursing decision support.